Comparing the efficacy of different intra-articular injections for knee osteoarthritis: A network analysis. Issue 31 (5th August 2022) - Lin, Xingzhen; Zhi, Fang; Lan, Qin; Deng, Weixiong; Hou, Xinju; Wan, Qing
Abstract : Background: The findings on the effectiveness of platelet-rich plasma, ozone, and hyaluronic acid in the treatment of osteoarthritis of the knee are controversial, and the existing original studies and meta-analyses are mostly comparisons of a single joint cavity injection method, lacking direct and indirect comparisons of different drugs in the joint cavity. The lack of direct and indirect comparisons of different drugs in the joint cavity makes it difficult to have a clearer and more comprehensive understanding of joint cavity injection methods. In this study, the efficacy of platelet-rich, ozone, sodium hyaluronate, and combined knee cavity injections were compared directly or indirectly using a reticulated meta-analysis in this field, and the efficacy of treatment measures was ranked to provide more comprehensive and reliable evidence-based clinical evidence for the selection of knee cavity injections in osteoarthritis of the knee. Objective: To compare the effects of platelet-rich plasma, ozone, and sodium glassate injection interventions on the efficacy of osteoarthritis of the knee through reticulated Meta-analysis, and to comprehensively compare the clinical effectiveness of platelet-rich plasma, ozone, and sodium glassate injection joint cavity injection for the treatment of osteoarthritis of the knee. Methods: The PubMed, CBM, CNKI, VIP, and Wan-Fang databases were searched for information on the effectiveness of platelet-rich plasma, ozone, and sodium vitrate injection for the comparative treatment of osteoarthritis of the knee, with a search time frame of each database from the date of creation to July 20, 2021. Two investigators independently screened the literature, extracted data according to inclusion and exclusion criteria, and evaluated the quality of the literature in parallel. Statistical analysis was performed using Stata 16.0 software to compare the differences in the efficacy of each treatment measure using the ratio and 95% confidence interval as effect indicators and to rank the efficacy. Results: Thirty-three RCTs with 7003 patients with osteoarthritis of the knee were included, involving 5 therapeutic measures. Meta-analysis showed that the efficacy of platelet-rich plasma injection was superior to both ozone and hyaluronic acid therapies. Hyaluronic acid+ozone and platelet-rich plasma+hyaluronic acid were both superior to ozone and hyaluronic acid monotherapy. The differences in efficacy between hyaluronic acid and ozone compared with platelet-rich plasma were statistically significant, and the differences in efficacy between the 2 combination therapies (platelet-rich plasma+hyaluronic acid, hyaluronic acid+ozone) and the 3 monotherapies (platelet-rich plasma, ozone, hyaluronic acid) were statistically significant. Platelet-rich plasma+hyaluronic acid, hyaluronic acid+ozone compared with 3 monotherapies (platelet-rich plasma, ozone, hyaluronic acid) were statistically significant, except for the difference in efficacy with platelet-rich plasma, which was not statistically significant, indicating that this platelet-rich plasma+hyaluronic acid and Hyaluronic acid+ozone combination therapy was superior to monotherapy. Also, the efficacy of platelet-rich plasma was better than hyaluronic acid and ozone and the difference was statistically significant, indicating that platelet-rich plasma was more effective than ozone and sodium glass in the treatment of osteoarthritis of the knee in monotherapy. Conclusion: It is believed that in the course of clinical practice, hyaluronic acid+ozone or platelet-rich plasma+hyaluronic acid combination therapy or platelet-rich plasma therapy can be preferred for patients with osteoarthritis of the knee.